SPA on Rabin variant with public key N= p2q - Abd Ghafar, Amir Hamzah; Kamel Ariffin, Muhammad Rezal (Springer, 2016)
Variants of the Rabin cryptosystem are built to overcome the decryption failure problem encountered by the cryptosystem. In this paper, we perform a theoretical simple power analysis on one of the variants that operates its decryption procedure via modular multiplication where the moduli N1=pq is kept secret while the moduli N=p2q is public. The attack utilizes Legendre’s theorem of continued fraction to successfully retrieve the secret key of the cryptosystem. An example of the attack is also included in this paper.